Identification and Functional Characterization of a Novel Bacterial Type Asparagine Synthetase A: A tRNA SYNTHETASE PARALOG FROM LEISHMANIA DONOVANI - Manhas, Reetika (American Society for Biochemistry and Molecular Biology, 2014)
Asparagine is formed by two structurally distinct asparagine synthetases in prokaryotes. One is the ammonia-utilizing asparagine synthetase A (AsnA), and the other is asparagine synthetase B (AsnB) that uses glutamine or ammonia as a nitrogen source. In a previous investigation using sequence-based analysis, we had shown that Leishmania spp. possess asparagine-tRNA synthetase paralog asparagine synthetase A (LdASNA) that is ammonia-dependent. Here, we report the cloning, expression, and kinetic analysis of ASNA from Leishmania donovani. Interestingly, LdASNA was both ammonia- and glutamine-dependent. To study the physiological role of ASNA in Leishmania, gene deletion mutations were attempted via targeted gene replacement. Gene deletion of LdASNA showed a growth delay in mutants. However, chromosomal null mutants of LdASNA could not be obtained as the double transfectant mutants showed aneuploidy. These data suggest that LdASNA is essential for survival of the Leishmania parasite. LdASNA enzyme was recalcitrant toward crystallization so we instead crystallized and solved the atomic structure of its close homolog from Trypanosoma brucei (TbASNA) at 2.2 Å. A very significant conservation in active site residues is observed between TbASNA and Escherichia coli AsnA. It is evident that the absence of an LdASNA homolog from humans and its essentiality for the parasites make LdASNA a novel drug target.